2007
DOI: 10.1016/j.biologicals.2006.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of pseudorabies virus genome-based transfer vehicle carrying major antigen sites of S gene of transmissible gastroenteritis virus: Potential perspective for developing live vector vaccines

Abstract: Two severe porcine infectious diseases, pseudorabies (PR) and transmissible gastroenteritis (TGE) caused by pseudorabies virus (PRV) and transmissible gastroenteritis virus (TGEV) respectively often result in serious economic loss in animal husbandry worldwide. Vaccination is the important prevention means against both infections. To achieve a PRV genome-based virus live vector, aiming at further TGEV/PRV bivalent vaccine development, a recombinant plasmid pUG was constructed via inserting partial PK and full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…2). Moreover, the immunomodulatory capacity of adenoviruses has been demonstrated using murine bone mar- [194] row-derived DC, in terms of maturation of the DC [42][43][44][45][46], phenotypic modification [42,47,48], and cytokine induction [42,[45][46][47][48][49]. Related to this, Miller et al [43] noted that the induced maturation of DC depended on virus entry rather than transcription of the viral genome, while Molinier-Frenkel et al [44] identified the penton capsomer and the fibre protein (and its knob domain) as major inducers of DC maturation.…”
Section: Adenovirus Interaction With DCmentioning
confidence: 99%
“…2). Moreover, the immunomodulatory capacity of adenoviruses has been demonstrated using murine bone mar- [194] row-derived DC, in terms of maturation of the DC [42][43][44][45][46], phenotypic modification [42,47,48], and cytokine induction [42,[45][46][47][48][49]. Related to this, Miller et al [43] noted that the induced maturation of DC depended on virus entry rather than transcription of the viral genome, while Molinier-Frenkel et al [44] identified the penton capsomer and the fibre protein (and its knob domain) as major inducers of DC maturation.…”
Section: Adenovirus Interaction With DCmentioning
confidence: 99%
“…Consequently, development of PRV-based vector vaccines was only recently resumed. Publications originate mainly from research institutes in China and report PRV recombinants expressing antigens from Japanese encephalitis virus (JEV) [109], FMDV [110] porcine reproductive and respiratory syndrome virus (PRRSV) [111][112][113], transmissible gastroenteritis virus (TGEV) [114], porcine circovirus 2 (PCV2) [115], FMDV plus porcine parvovirus (PPV) [116], rabies virus [117] and H3N2 swine influenza virus [118]. Data on vaccination/challenge experiments of these potential vaccine candidates are available for the recombinants expressing NS1 of JEV [109] VP1 of FMDV [110], GP5 of PRRSV [111][112][113], and haemagglutinin H3 of swine influenza virus [118].…”
Section: Herpesvirusmentioning
confidence: 99%
“…(2) The SARS-CoV genome contains five major open reading frames (ORF) that encode the replicase polyprotein; the spike (S), envelope (E), and membrane (M) glycoproteins; and the nucleocapsid protein (N). (3) The coronavirus S protein plays important roles in inducing the neutralizing antibody, (4)(5)(6)(7) interaction with specific cellular receptors, (8)(9)(10) host cell tropism, (11,12) hemagglutination, and sialic acid binding activity. (13,14) In addition, the S protein has been shown to be a virulence factor in various coronaviruses.…”
Section: Introductionmentioning
confidence: 99%